The Impact of Covid-19 Blame-Game Towards Anti-Asian Discrimination Phenomena - Aria Adibrata, Jordan; Fikhri Khairi, Naufal (The Journal of Society and Media, 2022)
This paper aims to describe the relationship between foreign policies based on the 'Blame Game' and the effect to society’s social conditions, especially in terms of discrimination against Asians. The debate over who should be responsible for the Covid-19 pandemic has brought tense to international political conditions. China's defensive foreign policy strategy turned out to be aggressive and even distorted information regarding the truth of the origins of the pandemic. Thus, Blame Game is destructive, uncooperative, and creating unresolved problems dealing with global pandemic that requires collective action. This also leads to the increase of discrimination acts towards the Asian community. This paper uses an explanatory-qualitative method, with data collection techniques through literary study. Constructivism theory and the concept of Political Racism are used as analytical tools to explain the relationship between the research variables. As a result, political elites create identities through the blaming game on various media platforms, especially social media, which impacts the creation of xenophobic perceptions toward the Asian community.